Evaluation of performances of different types of spray nozzles in site-specific pesticide spraying - Ali Bolat; Ömer Baris Özlüoymak (Semina: Ciências Agrárias, 2020)
In recent years, site-specific spraying methods, which are capable of combining the image processing technologies with electronic and information technologies, have been started to be used in the weed control and target-oriented spraying. In this study, in addition to the site-specific spraying in laboratory conditions; a mobile spraying system, which can also perform broadcast application as a reference method, was set up. The spraying performance of the mobile system was tested for three different nozzle types (standard flat fan nozzle, cone nozzle, air induction nozzle) and at speeds of 0.48, 0.60, 0.72 and 0.84 km h-1. The mobile system was operated as both broadcast and site-specific for each nozzle type and travel speed. Three artificial weed samples were used at 75 cm intervals as sampling surfaces on the movement of the mobile system in the spraying operations; filter papers (FP) and water-sensitive papers (WSP) were placed behind them on the bars. While deposition values were measured with the filter papers, water-sensitive papers were used to measure the coverage rates. The spray distribution of the site-specific method in comparison with the reference method was investigated. According to the results, site-specific spraying applications did not cause any negative impact on depositions and coverage rates. The nearest results compared with the broadcast spraying were obtained with the air induction nozzle type at a speed of 0.48 km h-1 with a 60.5% deposition amount and 95.9% coverage rate.